2019
DOI: 10.1097/md.0000000000016768
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of polydioxanone thread embedding acupuncture compared to physical therapy in the treatment of patients with non-specific chronic neck pain

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The detailed process of calculating sample size is described in the protocol paper. 29 All applicants were provided a written explanation and an informed consent form, and received a full explanation of this trial.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The detailed process of calculating sample size is described in the protocol paper. 29 All applicants were provided a written explanation and an informed consent form, and received a full explanation of this trial.…”
Section: Methodsmentioning
confidence: 99%
“…Eligibility criteria were as follows: 14–16 , 29–33 A subject 1) is aged (19–65) years-old, and 2) have suffered from neck pain for over three months, 24 3) scores more than 40 mm on the visual analogue scale (VAS) at the time of screening, 4) is diagnosed with CNP by clinicians based on image examination, history taking, physical and medical examination, and 5) is willing and able to observe the intervention and follow-up assessments. The exclusion criteria were: An excluded subject 1) suffers radicular pain in the upper limb with the distribution of a particular nerve root, 2) demonstrates neurological abnormality, such as positive to special test, such as Bakody sign (shoulder abduction relief sign test), Spurling test, muscle atrophy, paraesthesiae (sensory deficits), hyporeflexia of deep tendon reflex, weakness, pathologic reflex, 3) demonstrates major spinal pathology, such as spondylitis, myelopathy, fracture, neoplasm, neuromyopathic scoliosis, congenital abnormality, 4) shows a history of spinal surgery or scheduled procedures during the study, 5) suffers from pain more severe than neck pain in another region, 6) suffers from uncontrolled low back pain, 31–33 7) shows a history of receiving TEA at the neck region in the past 6 months, 14 8) suffers from skin damage that is difficult to treat on the neck, 9) has shown hypersensitive reaction to previous acupuncture treatment, metal allergy, severe atopy, keloid, or other skin hypersensitivities, 10) suffers from hemorrhagic disease or factors that can affect hemostasis, such as the taking of antiplatelet drug or anti-coagulant, 11) is pregnant, or is planning pregnancy during the trial, 12) suffers from cardiovascular disease or uncontrolled diabetes, 13) shows history of major psychiatric or neurotic disability or cognitive instability, 14) shows history of alcoholism or drug abuse, 15) suffers from severe underlying disease requiring active therapy, or 16) was considered by the researcher to be inappropriate for this trial.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our systematic review protocol is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) statement guidelines. [ 21 ] The systematic review protocol is registered in INPLASY (2020110087;DOI: 10.37766/inplasy2020.11.0087).…”
Section: Methods and Analysismentioning
confidence: 99%